AI-Augmented Branding: Exploring The Impact Of Generative Design Tools On Visual Identity Development In The Creative Industry - Indrawati, Dhewani; Amanina, Nadya Ahla; Maulida, Laila (International Journal of Graphic Design, 2025)
This study explores how generative artificial intelligence (AI) is reshaping the way visual designers and educators work and think. With tools like Midjourney, Adobe Firefly, and DALL·E becoming more widely used, creative processes are evolving—raising new questions about who creates, what counts as original, and how creative labor is valued. Through a qualitative approach, this research draws on interviews and document analysis involving professional designers and design educators in Indonesia. The findings reveal a complex landscape: generative AI opens up new space for experimentation, speeds up workflows, and helps spark ideas. At the same time, it brings challenges—ethical concerns, growing reliance on automation, and the risk of losing touch with foundational design skills. In the classroom, AI is both a disruption and an opportunity, pushing educators to rethink traditional studio methods while also offering fresh ways to build curricula. The study emphasizes the importance of fostering critical awareness in using AI, developing ethical guidelines for creative work, and adapting educational strategies to keep pace with technological change. By shedding light on how generative AI is influencing visual design, this research contributes to broader conversations about creativity, authorship, and innovation in today’s digital era.